Evaluation of the antioxidant and in vivo anticancer activity of Excoecaria agallocha bark extract - Sultana, Sharmin (Brac University, 2020)
This thesis report is submitted in partial fulfilment of the requirement for the degree of Master of Science in Biotechnology, 2019.